Larvicidal Efficiency of Nocoz and Lambda Cyhalothrin Against Fourth Instar Culex Pipiens Larvae - Alwan, Sarah Qais (American Journal of Biology and Natural Sciences, 2026)
Abstract: Culex pipiens L. (Diptera: Culicidae) serves as a significant vector for several illnesses. This mosquito is extensively distributed globally. The activity of pesticides can influence mosquito populations by regulating their numbers, interfering with biological control mechanisms, or fostering the development of insecticide resistance. The current study was conducted to determine the effect of various concentrations of the insecticides Nocoz and Lambda-cyhalothrin against fourth-instar mosquito larvae 6-24 hours after treatment. The highest larval mortality rate with Nocoz was 100.0% at a concentration of 0.01 ml/L, while the lowest mortality rate, 26.6%, was observed at a concentration of 0.0025 ml/L. Similarly, the results showed that the highest mortality rate of fourth-instar larvae treatment with Lambda-cyhalothrin was 100.0% at a concentration of 0.01 ml/L, and the lowest mortality rate, 73.3%, was observed at a concentration of 0.0025 ml/L. Therefore, the results demonstrate that both Nocoz and Lambda-cyhalothrin have a lethal effect on mosquito larvae. Conclusion: The findings of this study demonstrated that both Nocoz and lambda cyhalothrin exhibit high efficiency against fourth instar larvae of cheiving 100 mortality at high concentration. Clear dose dependent relationship was observed with larval mortality increasing as the concentration increased.